Combined Aerodynamic Modifications Reduce Drag in MPV Vehicles: Modifikasi Aerodinamis Terpadu Mengurangi Hambatan Udara pada Kendaraan MPV - Adinda Maydana; A'rasy Fahruddin (Indonesian Journal of Innovation Studies, 2025)
General Background: Aerodynamic characteristics play an important role in vehicle performance because air resistance directly affects fuel consumption and maximum speed. Specific Background: Winglet bumpers and rear spoilers are commonly applied aerodynamic devices intended to regulate airflow around vehicles and reduce drag. Knowledge Gap: Although aerodynamic devices have been widely studied, limited experimental evidence directly compares the combined application of bumper winglets and rear spoilers on MPV-type vehicles under controlled wind tunnel conditions. Aims: This study aims to analyze the effect of bumper winglets, rear spoilers, and their combination on air drag acting on an MPV model. Results: Experimental testing was conducted in a wind tunnel using wind speed variations of 7 m/s, 8.5 m/s, and 10 m/s under four configurations: without modification, winglet bumper, rear spoiler, and combined modification. The results show that all aerodynamic modifications reduced drag force and drag coefficient compared with the unmodified model. The combined configuration produced the best result, achieving the largest drag coefficient reduction of 38% at 8.5 m/s. Novelty: This study directly compares individual and combined aerodynamic modifications on an MPV prototype using controlled wind tunnel testing. Implications: The findings indicate that the combined use of bumper winglets and rear spoilers offers a practical aerodynamic strategy for reducing drag and improving high-speed vehicle efficiency. Keywords: Aerodynamics, Drag Coefficient, Winglet Bumper, Rear Spoiler, Wind Tunnel Key Findings Highlights The combined configuration generated the lowest measured air resistance. The largest reduction was recorded at 8.5 m/s. Airflow became more stable with smaller wake formation behind the vehicle.